Motivational factors for pursuing dentistry as a profession in colleges of Karachi, Pakistan - Mohid Abrar Lone; Maham Muneeb Lone; Muneeb Ahmed Lone; Muhammad Saad Shaikh; Fahad Khan; Azeem Hussain Soomro (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the reasons that motivated students to seek admission in dental colleges, and to assess differences in the reasons between students studying in private and public dental colleges. Methods: The cross-sectional analytical study was conducted at two public-sector and four privatesector dental colleges in Karachi from June to September, 2018, and comprised students of first to final year of studies. Data was collected using a self-administered questionnaire. Students were asked to mark all reasons that they considered had been an influencing factor on their decision to opt for dentistry. Data was analysed using SPSS 21. Results: Of the 900 forms distributed, 814(90.4%) were collected with complete data; 182(22.4%) males and 632(77.6%) females. The overall mean age was 20.8±1.3 years. Of the total, 324(39.8%) students were from the public sector, while 490(60.2%) were at private colleges. A statistically significant difference was noted in professional and personal reasons cited by the two groups of students (p<0.05). Conclusion: It is of utmost importance that students shall be very clear regarding their expectations from a career to minimise chances of abandoning it midway or being professionally dissatisfied even after completing a degree. Keywords: Dental students, Profession, Motivational factors. (JPMA 70: 1393; 2020).